Intraperitoneal transfer of microRNA‐29b‐containing small extracellular vesicles can suppress peritoneal metastases of gastric cancer - Kimura, Yuki; Ohzawa, Hideyuki; Miyato, Hideyo; Kaneko, Yuki; Kuchimaru, Takahiro; Takahashi, Rei; Yamaguchi, Hironori; Kurashina, Kentaro; Saito, Shin; Hosoya, Yoshinori; Lefor, Alan Kawarai; Sata, Naohiro; et al. (Cancer science, 2023)
Small extracellular vesicles (sEV) contain various microRNAs (miRNAs) and play crucial roles in the tumor metastatic process. Although miR‐29b levels in peritoneal exosomes were markedly reduced in patients with peritoneal metastases (PM), their role has not been fully clarified. In this study, we asked whether the replacement of miR‐29b can affect the development of PM in a murine model. UE6E7T‐12, human bone marrow‐derived mesenchymal stem cells (BMSCs), were transfected with miR‐29b‐integrating recombinant lentiviral vector and sEV were isolated from culture supernatants using ultracentrifugation. The sEV contained markedly increased amounts of miR‐29b compared with negative controls. Treatment with transforming growth factor‐β1 decreased the expression of E‐cadherin and calretinin with increased expression of vimentin and fibronectin on human omental tissue‐derived mesothelial cells (HPMCs). However, the effects were totally abrogated by adding miR‐29b‐rich sEV. The sEV inhibited proliferation and migration of HPMCs by 15% (p < 0.005, n = 6) and 70% (p < 0.005, n = 6), respectively, and inhibited adhesion of NUGC‐4 and MKN45 to HPMCs by 90% (p < 0.0001, n = 5) and 77% (p < 0.0001, n = 5), respectively. MicroRNA‐29b‐rich murine sEV were similarly obtained using mouse BMSCs and examined for in vivo effects with a syngeneic murine model using YTN16P, a highly metastatic clone of gastric cancer cell. Intraperitoneal (IP) transfer of the sEV every 3 days markedly reduced the number of PM from YTN16P in the mesentery (p < 0.05, n = 6) and the omentum (p < 0.05, n = 6). Bone marrow mesenchymal stem cell‐derived sEV are a useful carrier for IP administration of miR‐29b, which can suppress the development of PM of gastric cancer. miR‐29b incorporated in mesenchymal stem cells (MSCs) derived exsosomes strongly inhibits mesothelial mesenchymal transition in vitro. Intraperitoneal transfer of the miR‐29b‐rich exosomes suppresses the development of peritoneal metastasis from gastric cancer in murine model.